2020
DOI: 10.1093/biosci/biaa081
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of US State Regulated Weed Lists: A Discordance between Biology and Policy

Abstract: Weedy and invasive plants threaten our food supply, native biodiversity, and the structure and function of ecosystems. The number and impact of these damaging plants are expected to continue to grow with ongoing global change. Some of the most common policy tools to help mitigate this threat are regulatory weed lists, which limit the importation and movement of listed plant species, but there has never been a comprehensive analysis of plants regulated in the United States. We analyzed US state regulatory lists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…While there were several taxa regulated consistently across the United States, most taxa were regulated in only one or two states (Figures 1 and 4). Because political boundaries often do not coincide with ecological boundaries, it is unlikely that neighbouring states are at risk from vastly different sets of species (Lakoba et al, 2020;McCubbins et al, 2013). In a recent study, Lakoba et al (2020) found that regulated species occur in distinct geographic regions within the United States, but regulated lists do not reflect this spatial clustering (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While there were several taxa regulated consistently across the United States, most taxa were regulated in only one or two states (Figures 1 and 4). Because political boundaries often do not coincide with ecological boundaries, it is unlikely that neighbouring states are at risk from vastly different sets of species (Lakoba et al, 2020;McCubbins et al, 2013). In a recent study, Lakoba et al (2020) found that regulated species occur in distinct geographic regions within the United States, but regulated lists do not reflect this spatial clustering (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…states will appear to have longer lists if they list a diverse genus, e.g. Oklahoma; Lakoba et al, 2020) and to more easily compare regulated taxa across states, we considered a genus as one listed taxon.…”
Section: Data Sourcesmentioning
confidence: 99%
See 3 more Smart Citations